Anatomia floral de espécies de Cyperaceae (Poales) - Monteiro, Mariana Maciel [UNESP] (2015)
Cyperaceae comprises about 5000 species with a worldwide distribution. The family is divided into two subfamilies: Mapanioideae (earlier divergent) and Cyperoideae that are distinguished from each other by the structure of their reproductive units. There is no consensus on whether these units are flowers or reduced inflorescences in Mapanioideae. In Cyperoideae, the reproductive units correspond to a spikelet whose structural variation difficults the understanding of the floral evolution in the subfamily. Therefore, this work aimed to study the anatomy and development of the reproductive units of Mapania pycnostachya and Hypolytrum schraderianum (Mapanioideae) and Rhynchospora consanguinea (Cyperoideae), in order to contribute to the understanding of the evolution of reproductive traits in Cyperaceae. Flowers and inflorescences in different developmental stages were collected and processed following usual light and scanning electron microscopy techniques. The development and vascularization of the reproductive units of M. pycnostachya and H. schraderianum show that the outer floral bracts develop before the stamens; the two stamens do not develop simultaneously and diverge at different levels; and a vascular plexus is formed in the reproductive axis. These characteristics, along with the presence of floral bracts between the stamens and gynoecium in M. pycnostachya, confirm that the reproductive units of the species studied are inflorescences. With the results from floral anatomy and vascularization of R. consanguinea, we propose a hypothetical evolutionary model for Cyperoideae, based on an ancestral trimerous-pentacyclic flower. According to this model, during the evolution of the subfamily, one of the sepals was lost, as well as the inner whorl of stamens and one carpel, reducing from a tricarpellate to a bicarpellate condition, which is supported by comparative analyzes of floral structure in the family. We concluded by these results...